The potential of atrium design to maximize the passive cooling effect for low-rise public buildings in Malaysia - Mohd Firdaus, Noorfarhana Alia; Ismail, Mohd Noorizhar; Sanusi, Aliyah Nur Zafirah; Abdullah, Fadzidah; Asif, Nayeem (IFERP Explore, 2023)
One of the passive design techniques is the atrium, which can have certain effects on a building inside environment. One of the key considerations when designing a building, especially in a hot, humid area, is the ventilation component. Natural ventilation has the ability to increase a building’s energy efficiency. It can be incorporated into the design of buildings to provide indoor airflow and provide comfortable experiences for the users of the buildings. The integration of an atrium which serve an area for air movement could enhance the cooling of a building. Apart from that, it is crucial to rethink the sustainable design of public buildings by reducing the energy consumption to minimal the greenhouse gas emissions for the environment. Hence, this research was executed to study the potential of atrium design to maximize the passive cooling effect for low-rise public buildings in Malaysia. It might help people appreciate the value of using natural ventilation while creating an atrium that is suitable for a hot, humid region.